Fecal Hemoglobin Concentration, a Good Predictor of Risk of Advanced Colorectal Neoplasia in Symptomatic and Asymptomatic Patients - Navarro, Mercedes; Hijos, Gonzalo; Ramirez, Teresa; Omella, Ignacio; Carrera-Lasfuentes, Patricia; Lanas, Ángel (Frontiers in Medicine, 2019)
Background. Periodical faecal immunochemical testing (FIT) is a cost-effective strategy in colon cancer screening programmes. FIT is also used as a diagnostic test in symptomatic patients. but data are scarce. Aim. To determine the association between FIT-Hb concentration and the risk of advanced neoplasia (AN) detected in colonoscopy in two different populations. Methods. The outcomes of colonoscopies performed after a positive FIT (> 117 ng/ml) (Sentinel Gold test) result were analysed in patients included within a population-based CRC screening programme (screening group) and, as diagnostic evaluation in symptomatic patients (symptomatic group). The study was performed between January 1st,2014 and October 31,2016. Data are reported Con as medians with interquartile ranges or frequencies and percentages. Positive predictive value (PPV) at arbitrary faecal haemoglobin concentrations were also reported calculated for AN. Results. We recruited 2742 patients who underwent a colonoscopy procedure, 1515 (53.5%) of them within the CRC screening programme. Patients in the screening group were younger (65.0±3.3 vs 66.2±13.4 years, p<0.001) and more frequently male (p<0.001) vs. the symptomatic group. Colonoscopy found more frequently neoplastic lesions in the screening compared to the symptomatic group (61.9% vs 44.8% p<0.001). Hb concentration in FIT was significantly higher in patients with AN compared with patients without AN in both groups (p<0.001). The age-adjusted risk of AN increased significantly in both groups according to FIT Hb concentration in the Quartile 3 (OR (95% CI): 2.94 (2.33–3.71) and Quartile 4 (OR: 5.52 (4.36–6.99). Males, in both groups showed a higher probability of presenting AN. FIT values were higher for left- than for right-sided AN in the screening, but not in the symptomatic group. Positive predictive values for AN were higher in the screening group in positive FIT tests (range 43.9% - 70.5%; 117 to > 1000 ng/ml) compared to those in the symptomatic group (36.3% – 52.5%). Similar trends were observed for cancer diagnosis alone. Conclusions. Male gender, age and FIT Hb concentration are predictors of risk of advanced adenoma and colorectal cancer and should be used to prioritise colonoscopy in patients with suspected advanced neoplasia, both in screening and in symptomatic patients.